The Role of Language in Portfolio Learning - Conrad, Dianne (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
Within the practice of recognizing prior learning (RPL), language issues –writing, the act of capturing language – are critically important facets of portfolio development. Using data drawn from a study of several postsecondary institutions in three countries, this paper examines the role and impact of language in portfolio development processes. Specifically, it considers the dynamics that contribute to learners’ finding appropriate language and their response to that journey, noting that learners pass through several stages of language growth, beginning with learning the language of academic life and recognizing the importance of that “new” language. The paper also discusses the impact of assessors’ use of language and considers the notion of learners’ transformation as they pass through the portfolio learning process.